2019
DOI: 10.1210/clinem/dgz143
|View full text |Cite
|
Sign up to set email alerts
|

Sample Timing, Diagnosis of Subclinical Thyroid Dysfunction and Mortality in Acute Myocardial Infarction: ThyrAMI1 Study

Abstract: Objective The objective of this study was to determine the impact of blood sample timing on the diagnosis of subclinical thyroid dysfunction (SCTD) and mortality in patients with acute myocardial infarction (AMI). Patients, Design, and Main Outcome Measures Patients with AMI had thyroid function evaluated on admission between December 2014 and December 2016 and those with abnormal serum thyrotropin (TSH) had repeat thyroid fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The median initial TSH level was 20 mIU/L, with higher values in the OH group (42 vs. 14 mIU/L). Patients who received treatment had a higher TSH (25 mIU/L, IQR, 13-43) when compared to those who did not receive LT4 treatment (12 mIU/L, IQR, [11][12][13][14][15][16][17][18][19], (p = 0.007). In the group of patients that were not treated with LT4, 50% were hemodynamically unstable at baseline when compared to the 21% of those who were treated.…”
Section: Clinical Presentation Laboratory and Imaging Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The median initial TSH level was 20 mIU/L, with higher values in the OH group (42 vs. 14 mIU/L). Patients who received treatment had a higher TSH (25 mIU/L, IQR, 13-43) when compared to those who did not receive LT4 treatment (12 mIU/L, IQR, [11][12][13][14][15][16][17][18][19], (p = 0.007). In the group of patients that were not treated with LT4, 50% were hemodynamically unstable at baseline when compared to the 21% of those who were treated.…”
Section: Clinical Presentation Laboratory and Imaging Resultsmentioning
confidence: 97%
“…In terms of diagnosis, the response changes in the thyroid axis as a reaction to acute illness can limit the ability of thyroid testing to assess thyroid function and guide management decisions. The timing of the TSH sample as it relates to the AMI and time of the day has been associated with variable TH levels [17,18]. For example, a study of 47 patients without previous use of TH admitted with AMI, noted a decrease in total T3 (~19% at 24-26 hours when compared to a sample that was obtained during the first 6 hours) and TSH levels (~51%, when comparing similar timeframes).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This understanding may help to prevent inappropriate diagnoses being made and unnecessary treatments being initiated [11]. A previous analysis of participants presenting with AMI demonstrated that sample timing has a significant impact on the diagnosis and prognosis of subclinical thyroid disease (SCTD) [12]. Therefore, it is important to study the prevalence of thyroid dysfunction in AMI patients and understand factors associated with these biochemical abnormalities.…”
Section: Introductionmentioning
confidence: 99%